I am Not What I Like: Endorsing Brands on Social Media Negatively Affects Consumers' Self-Evaluation. Issue 1 (February 2022) - Bernritter, Stefan F.; Loermans, Annemijn C.; W. Eigenraam, Anniek; Verlegh, Peeter W. J.
To what extent do consumers incorporate the identity of brands they endorse on social media into their self-concept? We argue that, contrary to popular belief, online brand endorsements may not necessarily lead to inclusion of the brand into the self and may, consequently, lead to contrast effects that negatively affect consumers' self-evaluations. We test our hypotheses across five studies and find that consumers who endorse a brand on social media subsequently negatively adjust their self-evaluations on traits that reflect the brand's key personality traits. This effect occurs only if they endorse the brand (i.e., by "liking" or "following" it), but not when they just visit the brand's social media page. Moreover, the effect is moderated by brand symbolism, with stronger effects if the brand is perceived to have low brand symbolism. The downwards shift in consumers' self-evaluations negatively affects brand outcomes. We also explore the role of incentives as counter mechanism. In conclusion, our findings reveal a dark side to promoting consumer endorsement of brands on social media, one with implications not only for consumers but also for brands.